2018
DOI: 10.1038/s12276-018-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

MSK1 functions as a transcriptional coactivator of p53 in the regulation of p21 gene expression

Abstract: Mitogen- and stress-activated kinase 1 (MSK1) is a chromatin kinase that facilitates activator-dependent transcription by altering chromatin structure through histone H3 phosphorylation. The kinase activity of MSK1 is activated by intramolecular autophosphorylation, which is initially triggered by the activation of upstream mitogen-activated protein kinases (MAPKs), such as p38 and ERK1/2. MSK1 has been implicated in the expression of p21, a p53 target gene; however, the precise connection between MSK1 and p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…T15 also showed hyper-activation of the ribosomal protein S6 kinase α-5 protein, MSK1 (log 2 FC(pMSK1 ser376 ) = +1.9; Figure 1 ). MSK1 is directly phosphorylated by MAPKs at serine 360, threonine 581, and threonine 700, and subsequently autophosphorylates at serine 376 for protein activation ( 37 ). Seemingly conflicting roles for MSK1 in breast cancer have been described: it shows tumor suppressor functions by acting as a transcriptional coactivator of P53 and mediating phosphorylation of histone H3 in the transcriptional activation of p21 ( 37 ), but has also been associated with epithelial-mesenchymal transition (EMT) and subsequent skeletal metastasis by histone H3 acetylation and phosphorylation of Snail, which downregulates E-cadherin to promote cellular migration and invasion ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…T15 also showed hyper-activation of the ribosomal protein S6 kinase α-5 protein, MSK1 (log 2 FC(pMSK1 ser376 ) = +1.9; Figure 1 ). MSK1 is directly phosphorylated by MAPKs at serine 360, threonine 581, and threonine 700, and subsequently autophosphorylates at serine 376 for protein activation ( 37 ). Seemingly conflicting roles for MSK1 in breast cancer have been described: it shows tumor suppressor functions by acting as a transcriptional coactivator of P53 and mediating phosphorylation of histone H3 in the transcriptional activation of p21 ( 37 ), but has also been associated with epithelial-mesenchymal transition (EMT) and subsequent skeletal metastasis by histone H3 acetylation and phosphorylation of Snail, which downregulates E-cadherin to promote cellular migration and invasion ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results highlight the complex nature of phosphorylation and acetylation cross-talk in regulating histone function. In other work, Ahn et al 165 in 2018 showed through in vitro assays that histone phosphorylation by mitogen-and stressactivated kinase 1 (MSK1) stimulated transcription at p53dependent gene promoters. To pinpoint the phospho-sites involved, they used GCE to encode pSer at sites Ser10 and Ser28 of histone H3, and showed that while both sites enhanced p53dependent gene transcription, phosphorylation at Ser10 had a greater impact.…”
Section: Chemicalmentioning
confidence: 99%
“…MSK1 and/or 2 are involved in the positive and negative regulation of gene expression. MSK1 and MSK2 are recruited to specific genes by a host of transcription factors, including p53, ELK1, NF-κB, and RARα, several of which are substrates of MSK1/2 (Ahn et al 2018). Induction of immediate-early gene expression is associated with MSK1/2 phosphorylation of histone H3 at Ser10 or Ser28.…”
Section: Msk1/2 and Regulation Of Gene Expressionmentioning
confidence: 99%